The effect of a mesenteric traction syndrome on internal carotid artery blood flow - Olesen, Niels D.; Egesborg, Astrid H.; Frederiksen, Hans-Jørgen; Svendsen, Lars B.; Secher, Niels H. (Frontiers in Anesthesiology, 2023)
Purpose: During abdominal surgery, manipulation of internal organs may induce a “mesenteric traction syndrome” (MTS) including a triad of flushing, hypotension, and tachycardia that lasts for approximately 30 min. We evaluated whether MTS affects internal carotid artery blood flow. Methods: This prospective cohort study included 27 patients aged 65 ± 11 years (mean ± SD) undergoing stomach resection (n = 12), esophageal resection (n = 14), or gastro-entero anastomosis (n = 1) during propofol-remifentanil and thoracic epidural anesthesia. Duplex ultrasound determined internal carotid artery blood flow, laser Doppler flowmetry assessed forehead skin blood flow, and near-infrared spectroscopy determined cerebral oxygenation. Development of MTS was defined by flushing within 60 min after incision. Results: Seven patients developed MTS 22 (20-26; median (IQR)) min after incision and at that time the change in heart rate (to 87 ± 13 vs. 70 ± 11 bpm; P = 0.0007) and skin blood flow (to 214 (134-269) vs. 84 (59-112) PU; P = 0.0044) was higher in the patients who developed MTS as compared to those who did not, while mean arterial pressure (63 ± 13 vs. 64 ± 14 mmHg; P = 0.1433), cerebral oxygenation (69 ± 9% vs. 63 ± 10%; P = 0.2485), and internal carotid artery flow (225 ± 53 vs. 203 ± 69 ml/min; P = 0.9529) were similar. Conclusions: Hemodynamic perturbations are observed in some patients in response to manipulation of the viscera but development of a MTS appears not to influence internal carotid artery flow. Clinical trial registration: clinicaltrials.gov. id: NCT02951273 (https://clinicaltrials.gov/ct2/show/NCT02951273?term=NCT02951273&rank=1)